Exploring the differences of integrated and spatially resolved analysis using integral field unit data: the case of Abell 14. Issue 2 (20th February 2020) - Akras, Stavros; Monteiro, Hektor; Aleman, Isabel; Farias, Marcos A F; May, Daniel; Pereira, Claudio B
ABSTRACT: We present a new approach to study planetary nebulae using integral field spectroscopy. VLT@VIMOS datacube of the planetary nebula Abell 14 is analysed in three different ways by extracting: (i) the integrated spectrum, (ii) one-dimensional simulated long-slit spectra for different position angles, and (iii) spaxel-by-spaxel spectra. These data are used to build emission-line diagnostic diagrams and explore the ionization structure and excitation mechanisms combining data from one- and three-dimensional photoionization models. The integrated and 1D simulated spectra are suitable for developing diagnostic diagrams, while the spaxel spectra can lead to misinterpretation of the observations. We find that the emission-line ratios of Abell 14 are consistent with UV photoionised emission; however, there are some pieces of evidence of an additional thermal mechanism. The chemical abundances confirm its previous classification as a Type I planetary nebula, without spatial variation. We find, though, variation in the ionization correction factors as a function of the slit's position angle. The star at the geometric centre of Abell 14 has an A5 spectral type with an effective temperature of T eff  = 7909 ± 135 K and surface gravity log( g ) = 1.4 ± 0.1 cm s −2 . Hence, this star cannot be responsible for the ionization state of the nebula. Gaia parallaxes of this star yield distances between 3.6 and 4.5 kpc in good agreement with the distance derived from a three-dimensional photoionization modelling of Abell 14, indicating the presence of a binary system at the centre of the planetary nebula.